INVESTIGATION OF THE FEATURES OF NICKEL-MODIFIED MORDENITE ZEOLITES - Patrylak, Lyubov; Voloshyna, Yuliya; Pertko, Olexandra; Yakovenko, Anzhela; Povazhnyi, Volodymyr; Melnychuk, Oleksandr (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
Zeolites are wide used materials in a range of processes of chemical, petrochemical, and nutritional industry. They are the active catalysts and sorbents, in particular, zeolites are characterized by high efficiency towards extraction of heavy and radioactive metals from the aqua medium. An important factor of high zeolite catalyst activity is preserving the integrity of the crystal structure. The purpose of this research was to check out the features of MOR zeolite modifications with nickel by means of low temperature nitrogen adsorption/desorption, IR-spectroscopy, and X-Ray Diffraction (XRD). Using ion exchange and following calcination the hydrogen form of zeolite was obtained. The last was impregnated by nickel in quantity of 1, 5, and 15 wt. %. The investigations of nickel-modified samples demonstrated that MOR-type zeolite was relatively resistant to the used manipulations. However, the hysteresis loops of their isotherms are observed. The last can be connected with mesoporosity appearance. The degree of zeolite destruction is found out to increase with rise of nickel content in the samples. Based on IR spectra analysis by means of checking out the ratio between intensity of bands at 560 and 440 cm-1 using Gaussian function in Origin medium the same conclusions were drawn. Crystalline structure of mordenite was confirmed by using XRD method, but minor quantitative destruction cannot be recognized without application of methods of the internal and external standards.